1984
DOI: 10.3758/bf03205956
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory temporal integration as a function of pattern discriminability

Abstract: In a recent study, we measured temporal integration for vibrotactile spatial patterns presented to the fingertips. The patterns were generated on the tactile array of the Optaeon, a reading aid for the blind (Bliss, Katcher, Rogers, & Shepard, 1970;Craig, 1980). Several different tasks involving letter recognition were used in the study. In one task, letters were divided in half and the time between the presentation of the first and second half was varied, with the result that recognition performance declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These restrictive processes operate regardless of whether the pattern set is presented in a coherent display like a vibrotactile matrix, or one that limits the spatial integration of the patterns, as occurs on the separate fingers of the hand or over the body (see, e.g., Craig, 1984;Craig et al, 1985). It is also possible that such limitations may playa role in the discrimination of letter-like patterns (Craig, 1984;Evans, 1987;Horner, 1991Horner, , 1992. Such factors may be central to why most users of tactile aids report slow rates in processing of tactile information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These restrictive processes operate regardless of whether the pattern set is presented in a coherent display like a vibrotactile matrix, or one that limits the spatial integration of the patterns, as occurs on the separate fingers of the hand or over the body (see, e.g., Craig, 1984;Craig et al, 1985). It is also possible that such limitations may playa role in the discrimination of letter-like patterns (Craig, 1984;Evans, 1987;Horner, 1991Horner, , 1992. Such factors may be central to why most users of tactile aids report slow rates in processing of tactile information.…”
Section: Discussionmentioning
confidence: 99%
“…The three body loci will be tested with vibrotactile arrays specifically designed to match the spatial acuity of each (i.e., with varied contactor spacing), allowing examination of the sites under equivalent conditions (see, e.g., Cholewiak & Craig, 1984;Daley & Singer, 1975). In these arrays, the contactor separation is only slightly larger than the error of localization on the corresponding site.…”
Section: Apparatusmentioning
confidence: 99%
“…Several experimental paradigms can be generated from the situation in which there are two patterns presented sequentially, and there are either one or two sites ofstimulation. The two patterns may be sequentially presented to the same site, and the subject required to combine them-a temporal integration task (Craig, 1982a(Craig, , 1984. The two patterns may be presented to separate sites, and the subject required to combine or compare the two patterns-a divided attention task (Craig, 1985).…”
Section: Indiana University Bloomington Indianamentioning
confidence: 99%
“…The delivery of tactile information for abstract No paresthesia acquisition or transfer concepts has been found to be difficult. Craig (2000) found an accuracy rate of 30-60% for vibrotactile letter learning, while likewise Foulke and Broadbeck (1968) found a 40.4% error rate in teaching Morse code letters using electrocutaneous stimulation. Tactile task difficulty is one reason why tactile interfaces that require complex information processing are sparse.…”
Section: Discussionmentioning
confidence: 95%
“…The accuracy results from the present study are in agreement with previously established accuracy data regarding tactile letter acquisition. For example, Craig (2000) found accuracy performance in the range of 30-60% correct when vibrotactile letters were presented. Foulke and Broadbeck (1968) conducted a study that also found poor performance accuracy when they attempted to use electrocutaneous stimuli to deliver Morse code to participants at an isolated location.…”
Section: Discussionmentioning
confidence: 96%